EXPERIENCE IN CONDUCTING VIR ON WELLS OPERATING GAS CONDENSATE DEPOSITS OF THE BEREGOVOYE FIELD - E. V. Vaganov; E. Levitina; I. I. Krasnov; V. F. Tomskaya (Наука. Инновации. Технологии)
Introduction. The set of measures to increase the productivity of wells and increase gas and condensate recovery includes waterproofng works to restrict the infow of formation and bottom water. At the stage of development of gas condensate deposits of the Beregovoye feld, vertical and horizontal wells are fooded during operation due to poor-quality cementing along the annulus. This phenomenon leads to a complication in the form of a decrease in gas and condensate production rates, the creation of sand plugs, the formation of gas hydrates, which negatively affects the productivity index of wells. The increase in the idle well stock due to the fooding of the gas condensate reservoir of the BT10 and BT11 formations indicates the low effciency of the introduced water shut-off technologies. Materials and methods of research. The problem of limiting the breakthrough of formation water in wells operating gas condensate deposits of the BT10 and BT11 formations of the Beregovoye feld requires attention from the side of the applied insulating compounds and materials. This is due to the fact that, along with a large number of used waterproofng solutions, some of the water-soluble compositions are not very effective. To ensure high-quality isolation of water infow, plugging compounds must have the following properties: the reagent must be well fltered and retain this property during its injection; the setting time of the composition should be easily regulated; the composition must be resistant to dilution by formation waters and maintain stability at the temperature and pressure of the well for the entire period of water shut-off works (VIR). Results and Discussion. In order to determine the technical condition and identify the place of water infow into the wellbore, the branch of the UGE "Yamalpromgeofzika" carried out feld geophysical surveys (PLT) in a working well. As a result of the research, it was revealed that by the nature of the behavior of the temperature logging curves, there is a behind-the-casing crossfow from the bottom with an exit into the interval of opening the formation. The results of pilot tests of the integrated technology of water shut-off works at gas condensate wells in Western Siberia felds have shown its effectiveness. Conclusion. Based on the results of the performed geological and technical measures to eliminate the behind-the-casing fows from the underlying aquifer, an increase in the productivity factor can be explained. Thus, an increase in the fow rate during the current studies showed the following: the total fow rate according to the results of production logging before VIR was 47 thousand m3 / day (on a ø12 mm washer). Based on the results of these studies, the total fow rate of well № 156, operating the gas condensate reservoir of the BT10 formation of the Beregovoye feld, was 106 thousand m3 / day.